HUBUNGAN EXPLOSIVE POWER OTOT TUNGKAI DAN KOORDINASI MATA-KAKI DENGAN ACCURACY SHOOTING PADA TIM SEPAK BOLA SMA NEGERI 1 DUMAI - Arif Rahman Wahid; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The problem of this research is not optimal of leg muscle power and coordination eye-leg to do shooting football. This research was conducted to determine whether there is relationship of explosive leg muscle power and coodination of eye-leg with shooting accuracy on the football team of SMA N 1 Dumai. Sample in this study is the football team of SMA N 1 Dumai and totaled 18 people. The technique to collecting of sample was ( total sampling). The instrument of this research is test vertical power test jump which aims to measure the skill of shooting a ball. After that processing data with statistic, to test for normality with lilifor test at significant level α0,05. Based on the result of research, it can be concluded as follows. Of the result obtained explosive leg muscle power has no significant relationship with the result accuracy shooting on the football team of SMA N 1 Dumai rcount(0,178) < rtab (0,468), of the result obtained coordination eye-leg has a significant connection with teh result accuracy shooting on football team of SMA N Dumai because , rcount(0,607) > rtab (0,468), there is significant relationship together between explosive leg muscle power and coordination eye-leg against result acuracy shooting on fotball team of SMA N 1 Dumai because Rcount (0,706) >Rtab (0,468).Key words : Explosive Leg Muscle Power, Coordination Eye-Leg, Accuracy Shooting.